2015
DOI: 10.5430/jnep.v5n5p73
|View full text |Cite
|
Sign up to set email alerts
|

Personal characteristics and styles of coping with stress of nursing students of a university in Turkey

Abstract: Objective: University studentship and the university life itself have the potential to create worry and stress. Nursing education is a hard and stressful process. The purpose of this study is to identify nursing students' ways of coping with stress. Methods: The study was designed as a descriptive and cross-sectional. Target population of this study was all the students who were enrolled in a nursing school of a university located in Turkey. The data were collected "Personal Information Form", developed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
(25 reference statements)
0
10
0
1
Order By: Relevance
“…; Yesil et al. ). Among the studies reporting the utilization of problem‐focused coping strategy, the most common strategy used to deal with stressors was problem‐solving behaviours (Al Zayyat & Al Gamal ; Chen & Hung ; Hamaideh et al.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…; Yesil et al. ). Among the studies reporting the utilization of problem‐focused coping strategy, the most common strategy used to deal with stressors was problem‐solving behaviours (Al Zayyat & Al Gamal ; Chen & Hung ; Hamaideh et al.…”
Section: Resultsmentioning
confidence: 98%
“…(), Bahadır‐Yılmaz () and Yesil et al. () assessed coping ways in Turkish nursing students using the Revised Ways of Coping Strategies Questionnaire. These nursing students cited a self‐confident approach as their main coping strategy to cope with academic and clinical stressors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of social support and EI skills by nursing students are in keeping with other study results. [18][19][20][21][25][26][27] Also, in this study, participants reported multiple social support providers, although the size of their social support network was not determined. Lastly, the significant relationship among the three scales of social support: emotional, venting of emotions and instrumental is a selfexplanatory phenomenon and validate the measure used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[18,19] Similarly, in Turkey, a recent study found that nursing students who were seeking social support coped better with stress. [20] Further, a study found that nursing students with high EI also reported a large social support network. [21] Both high EI and a large social support network enabled nursing students to better deal with stress through the mediating influence of effective, multiple social interactions.…”
Section: Introductionmentioning
confidence: 99%